Has COVID-19 Changed Crime? Crime Rates in the United States during the Pandemic - Boman, John H. (American journal of criminal justice, 2020)
In response to the COVID-19 pandemic, state-level governments across the United States issued mandatory stay-at-home orders around the end of March 2020. Though intended to stop the spread of the COVID-19 virus, the lockdowns have had sweeping impacts on life in ways which were not originally planned. This study’s purpose is to investigate the extent to which governmental responses to COVID-19 have impacted crime rates in the U.S. Compared to the pre-pandemic year of 2019, crime – as measured by calls for service to law enforcement – has decreased markedly. However, there are multiple indications that the crime drop is being driven by decreases in minor offenses which are typically committed in peer groups. At the same time, serious crimes which are generally not committed with co-offenders (namely homicide and intimate partner violence) have either remained constant or increased. As such, the crime drop appears to be hiding a very disturbing trend where homicides remain unchanged and intimate partner batteries are increasing. Since many offenders would presumably be committing less serious crimes in a non-pandemic world, we raise attention to the possibility that mandatory lockdown orders may have taken minor offenders and placed them into situations where there is rampant opportunity for intimate partner violence, serious batteries, and homicides. While crime in the U.S. appears to be down overall, this good news should not blind us to a troubling co-occurring reality – a reality that paints a dim picture of unintended consequences to public health and criminal justice finances as a result of COVID-19 lockdowns.